Sensing the Same Space – Spatial Understanding and Engagement in Higher Education - Jyri Lindén; Mikko Kanninen; Reijo Kupiainen; Johanna Annala (Dansk Universitetspaedagogisk Tidsskrift, 2019)
The aim of this theoretically oriented review is to examine the role of space and spatial thinking in the changing teaching and learning environments in higher education. The starting point is that educational space is not a pre-set institution or only a physical space but a social construction. As such, space is a crucial element in the learning process and student engagement.